Sharia Economic Review of Gold Selling Price Determination: (Case Study at the Cempaka Indah Gold Shop, Talang Babat Village) - Tamam, Badrul; Nisak, Sayida Khoiratun (CV. Zabags Qu Publish, 2024)
This research aims to find out how Sharia Economic Review on Determining Gold Selling Prices (Case Study at the Cempaka Indah Gold Shop, Talang Babat Village). and the results of this research; First, gold traders have a very strong position in the marketing mechanism for gold buying and selling transactions because the level of stability of the gold business is very stable. In this gold buying and selling transaction, gold traders carry out price dualism. The price of gold sold by traders to buyers is always very different from the price of gold sold by buyers to traders. Second, the price of gold for consumers is always higher than the standard price because gold as jewelry is more expensive because of the aesthetic value and complexity of the jewelry design. Third, the government never sets the price of gold so respondents' answers are still very ambiguous. Because they do not yet understand the dominance and power of gold traders in marketing mechanisms and gold price movements. Fourth, the practices carried out by East Tanjung Jabung Marketing to increase or decrease the price of gold are not in accordance with Islamic law.